Challenges to admissions in the extended curriculum programme in the Faculty of Business and Management Sciences - Leshoro, T.M.; Jacobs, A. (South African Journal of Higher Education, 2019)
The challenges that beset the ECP/FBMS (Extended Curriculum Programme/ Faculty of Business and Management Sciences) at the beginning of the year emanate mainly from the admissions and registration constraints. These constraints could however, be successfully addressed at faculty and institutional level. Of all the stakeholders, students and lecturers mainly bear the brunt of these challenges. Amongst the ECP students, there are two significant groups- those from the rural areas where technology is still lacking and those from townships where the technology is theoretically available but not always in practice. The great majority is faced with teachers who are not good enough; hence they all end up struggling to cope with university standards. A question naturally arises as to how the university responds to the continuous and prolific challenges of first year students. One approach that can be used to remedy the situation may lie in changes to the current admission policy that may better serve all students, both ECP and mainstream.